2016
DOI: 10.31235/osf.io/qm8wj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Managing the carbon rift: Social metabolism, geoengineering and climate capitalism

Abstract: The idea that climate geoengineering could be used in conjunction to reducing greenhouse gas emissions to avoid catastrophic climate change has gained credence in both scientific and policy circles. Because of the inherent uncertainty about the risks involved, debates on the topic abound. Scientists agree that more research is needed on both the potential impacts of geoengineering on humans and ecosystems, and the governance mechanisms that would be the most appropriate for conducting field research and for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the discussions, such participants instead reinforced arguments as to why GGRs themselves might not materialize in practice (cf Thoni et al, 2020; Waller et al, 2020), suggesting that GGR promises should be treated sceptically, and implicitly making a case for protections against mitigation deterrence, rather than a case to dismiss it. Moreover, unlike many other promises, exaggeration about GGR cannot be rationally dispelled in ‘real-time’, because GGR acts as a ‘time-machine’ in climate policy, being able to promise future reversal of current and past emissions, and thus becoming a ‘temporal’ socio-ecological fix (cf Ekers and Prudham, 2017; Sapinski, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the discussions, such participants instead reinforced arguments as to why GGRs themselves might not materialize in practice (cf Thoni et al, 2020; Waller et al, 2020), suggesting that GGR promises should be treated sceptically, and implicitly making a case for protections against mitigation deterrence, rather than a case to dismiss it. Moreover, unlike many other promises, exaggeration about GGR cannot be rationally dispelled in ‘real-time’, because GGR acts as a ‘time-machine’ in climate policy, being able to promise future reversal of current and past emissions, and thus becoming a ‘temporal’ socio-ecological fix (cf Ekers and Prudham, 2017; Sapinski, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of 'over-optimistic assumptions' or 'unreliable expectations' of the feasibility of GGR has been highlighted in recent reviews of the GGR included in countries' low-emission development plans (Thoni et al, 2020) and of particular GGR techniques (Waller et al, 2020). 1 Other scholars have suggested that GGR innovations and promises might be understood as prospective spatio-temporal fixesfollowing Harvey (2003) and Jessop (2006) in which not only engineered technologies and infrastructures but also managed landscapes and biophysical processes are enrolled as responses to capitalist crises (Carton, 2019;Ekers and Prudham, 2017;Sapinski, 2016). In previous and parallel work (Markusson et al, 2018, forthcoming), we locate such technological promises as a key element in the cultural political economy (CPE) of climate change, in which innovation narratives and imaginaries are simultaneously a product of, and a means to sustain hegemonic economic power, via concepts and processes particularly including commodification (Jessop, 2009;Sum and Jessop, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of such ''internalization'' turns on the fact that molecular processes of capital accumulation are running up against a series of ecological and climatic limits. Myriad socio-ecological fixes are being deployed to circumvent, overcome, and indeed internalize these limits under the guise of ''green capitalism'' (Bu¨scher and Fletcher, 2015;Mann and Wainwright, 2018;McCarthy, 2015;Prudham, 2009;Sapinski, 2016a;Wanner, 2015;Nelson, 2015). Yet climate change portends a systemic underproduction crisis-the ''second contradiction of capitalism''-whereby exhaustion of key socio-ecological relations that underpin the creation of capitalist value can engender crises via rising costs, loss and damage, depreciation of assets, onerous regulation, and unproductive expenditures that restrict the capacity to generate surplus-value, and thus inhibit expanded accumulation (O'Connor, 1988; see also Ekers and Prudham, 2017;Fraser, 2014;Moore, 2015).…”
Section: Introductionmentioning
confidence: 99%